Protective effect of mannan oligosaccharides against early colonization by Salmonella Enteritidis in chicks is improved by higher dietary threonine levels - Santos, E. G.; Costa, F. G P; Silva, J. H V; Martins, T. D D; Figueiredo-Lima, D. F.; Macari, Marcos [UNESP]; Oliveira, C. J B; Givisiez, P. E N (Oxford University Press (OUP), 2013)
Aims: To evaluate mannan oligosaccharide (MOS) and threonine effects on performance, small intestine morphology and Salmonella spp. counts in Salmonella Enteritidis-challenged birds. Methods and Results: One-day-old chicks (1d) were distributed into five treatments: nonchallenged animals fed basal diet (RB-0), animals fed basal diet and infected with Salmonella Enteritidis (RB-I), animals fed high level of threonine and infected (HT-I), birds fed basal diet with MOS and infected (MOS-I), birds fed high level of threonine and MOS and infected (HT+MOS-I). Birds were inoculated at 2d with Salmonella Enteritidis, except RB-0 birds. Chicks fed higher dietary threonine and MOS showed performance similar to RB-0 and intestinal morphology recovery at 8 dpi. Salmonella counts and the number of Salmonella-positive animals were lower in HT+MOS-I compared with other challenged groups. Conclusion: Mannan oligosaccharides and threonine act synergistically, resulting in improved intestinal environment and recovery after Salmonella inoculation. Significance and Impact of the Study: Nutritional approaches may be useful to prevent Salmonella infection in the first week and putative carcass contamination at slaughter. This is the first report on the possible synergistic effect of mannan oligosaccharides and threonine, and further studies should be performed including performance, microbiota evaluation, composition of intestinal mucins and immune assessment. © 2012 The Society for Applied Microbiology.
Keywords: Food safety; Lactobacillus; Prebiotics; Salmonella; mannan; oligosaccharide; threonine; assessment method; bacterium; carbohydrate; colonization; food safety; infectivity; morphology; nutrition; pollution effect; poultry; animal experiment; animal food; animal salmonellosis; animal tissue; bacterial colonization; chick; comparative study; controlled study; diet supplementation; drug effect; male; nonhuman; protection; Salmonella enteritidis; small intestine; Animalia; Aves